Evaluation of fontanel size variation and closure time in children followed up from birth to 24 months - (:unkn) unknown (AMER ASSOC NEUROLOGICAL SURGEONS, 2018)
OBJECTIVE Anterior fontanel size and closure time can be useful clinical signs for the early diagnosis of diseases. Knowing age-related normal variations is important to decide on further investigations. The authors of this study aimed to describe fontanel size variation according to age, determine fontanel closure time, and identify the optimal method for assessing fontanel size. METHODS For this prospective cohort study, 321 healthy term babies who fulfilled the inclusion criteria were consecutively recruited. Percentile charts for the mean anterior fontanel size and oblique measurements from birth to 24 months of age were created. RESULTS The mean fontanel closure time was 9.7 +/- 5.0 months (girls 10.3 +/- 4.7 months, boys 9.2 +/- 5.1 months). No differences were observed between the traditional method and oblique measurements. Early fontanel closure was not associated with microcephaly. CONCLUSIONS Oblique measurements can be used because they are as accurate as the traditional method. Children with fontanels measuring above the 95th percentile should be monitored closely and investigated further for potentially associated diseases.
Keywords: anterior fontanel; anthropometry; child; infant; physical examination; diagnostic technique; ANTERIOR FONTANELLE; HEAD CIRCUMFERENCE; TERM; INFANTS